1984
DOI: 10.1016/s0022-5347(17)50231-1
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Bladder

Abstract: We report a case of carcinosarcoma of the bladder. Total cystectomy with ileal loop urinary diversion was performed. Histologically, the bulk of the tumor tissue was rhabdomyosarcoma and adenocarcinoma. At distant areas from the bulk tumor transitional cell carcinoma was noted. The literature is reviewed and the clinicopathologic condition of carcinosarcoma of the bladder is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Of the approximately 70 cases of primary heterologous carcinosarcoma of the urinary bladder hereto reported in the literature,7‐51 55 were found to be sufficiently documented. A review of those 55 cases,7‐9, 11‐22, 24‐27, 29‐42, 44‐51 as well as our 8 patients, is given in Table 1. There is a male preponderance among patients with heterologous carcinosarcomas of the urinary bladder, with a male‐to‐female ratio of 1.6:1 (39 of the 63 patients were males) and mean and median ages of 66.4 years and 71 years, respectively, (range, 21‐91 years),51, 53 figures similar to those for conventional urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the approximately 70 cases of primary heterologous carcinosarcoma of the urinary bladder hereto reported in the literature,7‐51 55 were found to be sufficiently documented. A review of those 55 cases,7‐9, 11‐22, 24‐27, 29‐42, 44‐51 as well as our 8 patients, is given in Table 1. There is a male preponderance among patients with heterologous carcinosarcomas of the urinary bladder, with a male‐to‐female ratio of 1.6:1 (39 of the 63 patients were males) and mean and median ages of 66.4 years and 71 years, respectively, (range, 21‐91 years),51, 53 figures similar to those for conventional urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly observed in the female genital tract1, 2 but may also be encountered in other locations, including the male genital system, lower and upper respiratory and urinary tracts, digestive tract, hepatobiliary system, salivary glands, pancreas, thyroid, thymus, skin, breast, spleen, and female peritoneum 3‐6. Heterologous carcinosarcomas of the urinary bladder are rare neoplasms; about 70 acceptable cases have been reported so far, most often as single reports or limited series 7‐51. Since the cumulative literature review of Young in 1987,51 little has been reported on heterologous carcinosarcoma of the urinary bladder, and the issues of the prognosis, treatment, and histogenesis of those tumors have rarely been specifically addressed.…”
mentioning
confidence: 99%
“…The term malignant mesodermal mixed tumor [1][2][3] is conventionally used as a synonym for carcinosarcoma [4][5][6][7][8][9]. Although, in 1975 in the urological field, Koss [10] first referred to a tumor that included heterologous components, such as bone, cartilage and striated muscle, as a malignant mesodermal mixed tumor, the histogenesis was not clarified.…”
Section: Discussionmentioning
confidence: 99%